Understanding Kant's ethics - Cholbi, Michael (Cambridge University Press, 2016)
Kant's ethical thought remains one of the most influential, yet notoriously challenging, systems in the history of philosophy. This volume provides a sympathetic but critical reconstruction of the main strands of Kant's ethics, focusing on the most commonly read of Kant's ethical works, the Groundwork of the Metaphysics of Morals. Part I outlines Kant's arguments in defense of his Categorical Imperative, as well as elaborating Kant's understanding of dignity and human freedom. Part II addresses the most common objections to Kant's ethics, including challenges to the Formula of Universal Law; Kant's controversial ethical stances on suicide, sex and marriage, and non-human animals; and the place of reason, sentiment, and happiness in Kant's ethics. For scholars and specialists alike, the volume offers a clear and accessible account of what Kantian morality both offers us and asks of us